The importance of co-receptors in antiretroviral therapy and novel studies on non-peptide, small molecule chemokine receptor type 5 (CCR5) antagonists - Dilek Aksoy; Füsun Göktaş Ur (İstanbul Journal of Pharmacy)
Human immunodeficiency virus (HIV) infection is a major health problem worldwide. Antiretroviral Therapy (ART) involves a combination of HIV drugs (called HIV treatment regimen). However, ART resis5 tance, which emerged because of evolutionary processes, poses numerous challenges in HIV treatment. Therefore, there is urgently needed to develop new anti5retroviral drugs that can eliminate resistant HIV strains. HIV interacts with the primary receptor cluster of differentiation 4 + T cell (CD4+ ) and its co5receptor to allow entry by triggering major structural rearrangements and inducing membrane fusion. Among chemokine receptors, the C5C chemokine receptor 5 (CCR5) is the main co5receptor for HIV binding, which is responsible for viral transmission. Therefore, CCR5 plays an important role in HIV pathogenesis. CCR5 antagonists block the binding of HIV51 to the CCR5 receptor, leading to the discovery of new drug molecules and the search for more effective therapeutics. This review focuses on CCR5 antagonists as viral targets and highlights relevant drug molecules consid5 ering advances in the structural biology of pharmacophore sites. In addition, this article reviews studies on existing drug molecules and discusses the development of CCR5 antagonists that can combat HIV51 infection.